THE HIGHER EDUCATION OF LEADERSHIP STRATEGY TO DEVELOPE ACADEMIC CULTURE - Khaeruman Khaeruman; Suflani Suflani; Fatari Fatari; Pramudi Harsono (SEAN Institute, 2022)
Higher education leaders play an essential role in the progress of the organization. The ability of university directors is needed to lead organizations, both in university policy, guiding students, motivating staff, and working with various parties. This research aims are: (1) How is the university's management strategy in developing researchers? (2) How is the implementation of university administration in the development of academic culture? (3) What are the factors in building an academic culture? This research used a qualitative approach conducted at Bina Bangsa University. Data collection techniques with interview techniques, observation, documentation. The data analysis step is carried out by summarizing, presenting, and drawing conclusions. The results of this study: 1) The strategy implemented by management has goals, objectives, stages and time. a) The aim of building an academic culture is based on the competitive and religious vision and mission of Bina Bangsa University. b) The purpose of building an academic culture is; lecturers and students. c) The stages of developing academic and religious culture are short term, long term and long term. d) time to build an academic culture; at the beginning, middle and end of the semester. 2) During the implementation of the academic program, namely: a) Implementation of an academic culture through recruitment, training and evaluation programs.